2017
DOI: 10.1007/978-3-319-55231-6_35
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Onset of Reoxygenation in Inactive Muscles After High-Intensity Exercise

Abstract: Oxygenation, measured by near-infrared spectroscopy (NIRS), in inactive muscles decreases during high-intensity exercise because of the decrease of oxygen supply. However, there have been few reports regarding recovery of inactive muscle oxygenation after exercise. This study was performed to examine reoxygenation in the biceps brachii muscle (BB) after supramaximal cycling exercise. Six active young male volunteers (age: 22  ±  3 years, peak oxygen uptake (VO): 53.8  ±  5.4 mL/kg/min, mean  ±  S.D.) performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 12 publications
0
11
1
Order By: Relevance
“…4, Panel D). Our results are the opposite of Osawa et al 14 , who investigated the recovery of BB after supramaximal cycling exercise with legs (140% of VO 2peak for 30 s and then no-load cycle exercise for 4 minutes). They observed that recovery of tissue oxygenation in biceps brachii did not occur immediately after effort and the reoxygenation in the arm was slower than in the leg.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…4, Panel D). Our results are the opposite of Osawa et al 14 , who investigated the recovery of BB after supramaximal cycling exercise with legs (140% of VO 2peak for 30 s and then no-load cycle exercise for 4 minutes). They observed that recovery of tissue oxygenation in biceps brachii did not occur immediately after effort and the reoxygenation in the arm was slower than in the leg.…”
Section: Discussioncontrasting
confidence: 99%
“…They observed that recovery of tissue oxygenation in biceps brachii did not occur immediately after effort and the reoxygenation in the arm was slower than in the leg. However, the exercise type adopted by Osawa et al 14 (cycling efforts for leg) and recovery process (arm in rest and leg in movement) are different that applied by us. In the light of our study, for high-intensity running exercise, the biceps brachii seems to play an important role during process recovery, which implies in future proposals of aerobic physical training to potentiate this muscle response.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations